(untitled) (Revista horizonte, 2014)
Objective: the purpose of this study was intended to determine the effects of a high-intensity interval training (HIIT) program by considering variables of maximum oxygen consumption (VO2 max), body fat percentage and muscular endurance on secondary school students. Methods: 23 subjects (n=23) were chosen on this quasi- experimental study; (fourteen women and nine men) from a semi-private school in Paillaco. vo2mAX was measured by Course Navette test, body fat percentage by using bioelectrical impedance and performance on endurance tests of squats, crunches and push-ups. Then, 24 sessions of HIIT were developed twice a week and the pre and post results were compared over the mentioned variables by using the Student’s t-distribution statistic (SPSS V18). RESULTS: With a 24 sessions HIIT program, a significant improvement (p<0,05) was found on the variables body fat percentage and an increase muscular endurance on abdominal arms, legs and abdominal tests. Conclusion: A HIIT program, developed twice a week, would be sufficient to produce changes on the body composition of the subjects; improve their VO2 max and muscular endurance. It is suggested to use this model on sedentary students as an effective and efficient method in relation to training periods and VO2max, significant reduction of performance enhancement